2016
DOI: 10.21037/atm.2016.03.27
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of BRCA1 expression on the efficacy of chemotherapy based on anti-microtubule agents: a pooled analysis across different malignancies and agents

Abstract: Background: Breast cancer susceptibility gene 1 (BRCA1) expression has been suggested as a predictor in antineoplastic treatment with anti-microtubule agents. However, the existing evidence is conflicting. Consulting the literature, we sought to examine the true impact of BRCA1 expression on the efficacy of anti-microtubule agents.Methods: Medline by PubMed and Embase databases were searched for eligible studies. The primary endpoints were objective response rate (ORR) and progression free survival (PFS). Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…It is worth noting that BRCA1 plays a pivotal role in DNA repair and cell cycle regulation in response to DNA damage, potentially resulting from chemotherapy and radiotherapy. Indeed, several studies reported that BRCA1 mRNA expression had predictive impact on responses to chemotherapy, as well as to chemoradiotherapy in many types of cancer, such as breast cancer, lung cancer, and esophageal cancer [ 27 , 28 , 29 , 30 , 31 ], suggesting BRCA1 as an attractive candidate for predicting nCRT response in LARC. It has been reported that GPR110 ( ADGRF1 ) can induce cell cycle arrest and chemoresistance in breast cancer [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that BRCA1 plays a pivotal role in DNA repair and cell cycle regulation in response to DNA damage, potentially resulting from chemotherapy and radiotherapy. Indeed, several studies reported that BRCA1 mRNA expression had predictive impact on responses to chemotherapy, as well as to chemoradiotherapy in many types of cancer, such as breast cancer, lung cancer, and esophageal cancer [ 27 , 28 , 29 , 30 , 31 ], suggesting BRCA1 as an attractive candidate for predicting nCRT response in LARC. It has been reported that GPR110 ( ADGRF1 ) can induce cell cycle arrest and chemoresistance in breast cancer [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A potential role for BRCA1 as a biomarker for sensitivity to vinorelbine was identified in 2012 [ 53 ], and potentially confirmed through a pooled analysis [ 54 ]. On the basis of this observation a Phase II clinical trial (NCT02139904) was conducted with patients randomized 2:1 to receive either active symptom control with oral vinorelbine versus active symptom control (ASC) every 3 weeks until disease progression, unacceptable toxicity or withdrawal [ 55 ], and whilst the trial met its stated primary goal with respect to improved PFS, BRCA1 did not predict resistance to ASC + vinorelbine [ 55 ].…”
Section: The “Mesothelioma Model”mentioning
confidence: 99%
“…Выдвинута гипотеза, что повышенный уровень экспрессии BRCA1 положительно коррелирует с чувствительностью опухолевых клеток к таксанам: в исследованиях, проводившихся на клеточных линиях с идуцированной экспрессией BRCA1, обнаружилось, что чувствительность этих клеток к таксанам была резко повышена [63]. У пациентов с РЖ, имеющих повышенную экспрессию BRCA1, наблюдались большая частота объективного ответа и выживаемость без прогрессирования при назначении ингибиторов митоза [64].…”
Section: другие прогностические маркерыunclassified